2013
DOI: 10.1159/000343369
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Stromal Lymphopoietin Over-Expressed in Human Atherosclerosis: Potential Role in Th17 Differentiation

Abstract: Background: Adaptive immunity plays a critical role in atherosclerosis and T helper 17 (Th17) cells, a new T-cell lineage, are recently reported to be involved in atherosclerosis. However, the mechanism underlying Th17 inflammation in atherosclerosis remains largely unknown. Thymic stromal lymphopoietin (TSLP) is a novel IL-7-like cytokine and mainly responsible for Th2 inflammation in many inflammatory diseases. Methods and Results: Immunohistochemistry showed that TSLP over-expressed in human atherosclerotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
0
22
0
2
Order By: Relevance
“…Although classified as a hematopoietin receptor based on its structural homology, the TSLPR subunit contains notable differences compared with the canonical hematopoietin receptors. Our previous study demonstrated that the inflammatory cytokine TSLP was over-expressed in human atherosclerotic artery specimens [27]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although classified as a hematopoietin receptor based on its structural homology, the TSLPR subunit contains notable differences compared with the canonical hematopoietin receptors. Our previous study demonstrated that the inflammatory cytokine TSLP was over-expressed in human atherosclerotic artery specimens [27]. …”
Section: Discussionmentioning
confidence: 99%
“…In general, TSLP is produced by epithelial cells and epidermal keratinocytes, and recent studies have demonstrated that several inflammatory cells, including dendritic cells (DC S ), smooth muscle cells, and cancer or cancer-associated cells, also express TSLP [19,21,22,23,24,25]. Recently, we demonstrated that TSLP could be induced to express in vascular endothelial and smooth muscle cells by angiotensin II and oxidized-low-density lipoprotein [26] and over-expressed in human atherosclerotic artery specimens [27], which indicated that TSLP/TSLPR might play roles in atherosclerosis. Therefore, TSLP is not only associated with inflammatory and allergy diseases but also plays important roles in atherosclerosis, which has been linked to platelet activation and the probability of thrombosis [28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Thymic stromal lymphopoietin (TSLP) mediates inflammation and is essential for allergic inflammation. In a preliminary study, we showed that TSLP plays an important role in the innate and adaptive immune system and is over-expressed in human atherosclerotic plaques [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…It mediates various types of allergic inflammation, such as atopic dermatitis and asthma, and plays an important role in the polarisation of dendritic cells (DCs) to drive T helper (Th) 2 cytokine production [11,12,15,16,17]. Ox-LDL can induce TSLP expression in human vascular smooth muscle cells (HVSMCs) and human umbilical vein endothelial cells (HUVECs), and angiotensin II can induce primary vascular smooth muscle cells (VSMCs) to express TSLP [8,9]. In addition, TSLP can promote the Th17 immune response in vitro , which may be implicated in Th17 inflammation in atherosclerosis through DC activation; Angiotensin II-induced TSLP enhances the Th17-driven immune response in atherosclerosis and hypertension [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…SGK1 has been most recently shown to participate in the signaling inducing pathogenic Th17 cells which drive autoimmune disease [11,12]. DCs and NF-κB signaling both participate in the regulation of Th17 cells [13,14]. The role of SGK1 in DCs has, however not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%